Upper crustal differentiation processes and their role in 238U-230Th disequilibria at the San Pedro-Linzor volcanic chain (Central Andes). (October 2020) - Godoy, Benigno; McGee, Lucy; González-Maurel, Osvaldo; Rodríguez, Inés; le Roux, Petrus; Morata, Diego; Menzies, Andrew
Abstract: U-series data are combined with major and trace element constraints to construct a detailed view of the magmatic system feeding the San Pedro-Linzor volcanic chain, aiding the understanding of how stratovolcanoes in extremely thick arc crust evolve. Lavas from the Quaternary San Pedro-Linzor volcanic chain (Central Andes) have ( 238 U/ 230 Th) ranging from 1.015 to 1.072, with 238 U excess even in the less evolved ( 57 wt% SiO2 ) analyzed lavas. Contrary to well-established trends between fluid mobile elements and 238 U excess, ( 238 U/ 230 Th)0 shows no systematic correlation with ratios indicative of fluid-driven melting (e.g. Ba/Hf and K/La). Moreover, the inverse correlation between ( 238 U/ 232 Th) with the amount of slab-derived fluid and the oxidation state of the mantle below Central Andes, which decreases eastwards, suggests that the main control of the 238 U excess is not associated with hydration of the mantle wedge. Changes in ( 238 U/ 232 Th) and ( 230 Th/ 232 Th)0 are observed with variations in SiO2 and CaO + Al2 O3 contents, and 87 Sr/ 86 Sr and Dy/Dy* ratios of the lavas. These changes correspond to increasing ( 238 U/ 232 Th) with decreasing Dy/Dy* and CaO + Al2 O3 ratios, which is attributed to changes in crystallization of mineralogical phases within magmatic chambers during differentiation. Also, 230 Th in-growth is produced during stagnation within magmatic chambers located below the San Pedro-Linzor volcanic chain. Finally, a positive correlation between ( 230 Th/ 232 Th)0 and 87 Sr/ 86 Sr indicates an important role of crustal contamination, and of new mafic inputs during evolution of the volcanic chain with time. Our observations suggest that better constraints of all magmatic processes are needed to fully understand the U-series disequilibria recognized for the different volcanic structures developed within subduction-related tectonic environments. Highlights: U-Th activity was measured at the San Pedro-Linzor volcanic chain (Central Andes). U-Th disequilibria was obtained in the volcanic products <270 ka of the chain. The disequilibria is related to magmatic processes at crustal levels <20 km depth. ( 238 U/ 232 Th) suggests amphibole fractionation, during which 230 Th in-growth occurs. Magmatic recharge causes a decreasing on the ( 230 Th/ 232 Th) in the last 100 ka.